Preferência de Oviposição de Grapholita molesta (Busck) (Lepidoptera: Tortricidae) em Cultivares de Pessegueiro - Montes, Sônia Maria Nalesso Marangoni; Boliani, Aparecida Conceição [UNESP]; Raga, Adalton; Paulo, Edison Martins (FapUNIFESP (SciELO), 2011)
The objective of this study was to evaluate the effects of infestation by Grapholita molesta on peach cultivars. Surveys were conducted on the number of branches attacked by cultivar through visual sampling of one hundred (100) branches in four periods in the years 2004, 2005 and 2006, preferably in the spring, when outbreaks of shoots occur in peachs. The cultivars Tropical, Aurora 2, Doçura 2, Ouromel 3, Jóia 4, Talismã, Dourado 2, Aurora 1, Regis, Rei da conserva, grafted on Okinawa and Umê were evaluated. The experimental design was randomized blocks, each one consisting of ten trees, with 5 replicates, the treatments represented by the periods of sampling. There was higher infestation of peach sprouts by Grapholita molesta in the spring, 2004 for the cultivars on Okinawa, and in the spring, 2006 for the cultivars on Umê, with damages of around 14, 85% and 14.27%, respectively. From the cultivars on Okinawa, cultivars Tropical, Aurora 2 and Rei da conserva were the most damaged by the pest, whereas Aurora 2 was the cultivar on Umê, most damaged.
Oviposition preference of Grapholita molesta (Busck) (Lepidoptera: Tortricidae) on peach cultivars
Keywords: Damage; Fruit moth oriental; Natural infestation; Prunus persica